(untitled) (LEARNing Landscapes, 2008)
Many years ago, Hugh MacLennan (1945) described the relationship between French and English speaking Canadians as "two solitudes." This paper contends that there are "two solitudes" in education that threaten the very essence of state-supported education. It will argue that policy makers have made schools the centres of blame and have adopted policies that fail to account for the realities of schools, teachers and students. It will also suggest ways to bridge the gap between policy and practice and develop schools as centres of change.